Attenuation of muscle wasting in murine C2C12 myotubes by epigallocatechin‐3‐gallate. Issue 4 (20th March 2014) - Mirza, Kamran A.; Pereira, Suzette L.; Edens, Neile K.; Tisdale, Michael J.
Abstract : Background: Loss of muscle protein is a common feature of wasting diseases where currently treatment is limited. This study investigates the potential of epigallocatechin‐3‐gallate (EGCg), the most abundant catechin in green tea, to reverse the increased protein degradation and rescue the decreased protein synthesis which leads to muscle atrophy. Methods: Studies were conducted in vitro using murine C2 C12 myotubes. Increased protein degradation and reduced rates of protein synthesis were induced by serum starvation and tumour necrosis factor‐α (TNF‐α). Results: EGCg effectively attenuated the depression of protein synthesis and increase in protein degradation in murine myotubes at concentrations as low as 10 μM. Serum starvation increased expression of the proteasome 20S and 19S subunits, as well as the proteasome 'chymotrypsin‐like' enzyme activity, and these were all attenuated down to basal values in the presence of EGCg. Serum starvation did not increase expression of the ubiquitin ligases MuRF1 and MAFbx, but EGCg reduced their expression below basal levels, possibly due to an increased expression of phospho Akt (pAkt) and phospho forkhead box O3a (pFoxO3a). Attenuation of protein degradation by EGCg was increased in the presence of ZnSO4, suggesting an EGCg‐Zn 2+ complex may be the active species. Conclusion: The ability of EGCg to attenuate depressed protein synthesis and increase protein degradation in the myotubule model system suggests that it may be effective in preserving skeletal muscle mass in catabolic conditions.